4x-9=2(2x+7)

Simple and best practice solution for 4x-9=2(2x+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-9=2(2x+7) equation:


Simplifying
4x + -9 = 2(2x + 7)

Reorder the terms:
-9 + 4x = 2(2x + 7)

Reorder the terms:
-9 + 4x = 2(7 + 2x)
-9 + 4x = (7 * 2 + 2x * 2)
-9 + 4x = (14 + 4x)

Add '-4x' to each side of the equation.
-9 + 4x + -4x = 14 + 4x + -4x

Combine like terms: 4x + -4x = 0
-9 + 0 = 14 + 4x + -4x
-9 = 14 + 4x + -4x

Combine like terms: 4x + -4x = 0
-9 = 14 + 0
-9 = 14

Solving
-9 = 14

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 11+3x=12+5x | | 0=3t-2t | | y=4tanx | | -9x-43=15-11x | | 6x-8x+2=-10 | | p-8.125=16.21 | | (-12)(-13)= | | 5r+10=3r+5-3r | | p-8.125p=16.21 | | 3x*13x+14*4=7 | | 6x-8y-9x-6y= | | x^4+18x^2+69= | | 8v-3v=25 | | -5x-7=11 | | 11x-3=10(x-5)-8 | | 4=5x-3 | | 6x^2-11x+5=3x+17 | | -x-42=4x+33 | | 126-36n=7+2n | | 6v-4=8(v-2) | | 73(3x)=10 | | -10x+2=12 | | 5x+8=4(x+6)+3 | | t^3+t^2-8m^3-4m^2=0 | | 2y-8=3y-10 | | 3(x-3)+2x-3=4x-8 | | 5x+4=8x-30 | | -2-42=4x+33 | | 15x*6=12 | | 62(30x-80)-43(52-20x)=377 | | -2k=1/4 | | x-14=5x+18 |

Equations solver categories